1947
DOI: 10.1149/1.3071841
|View full text |Cite
|
Sign up to set email alerts
|

A Theory for the Mechanism of Chromium Plating; A Theory for the Physical Characteristics of Chromium Plate

Abstract: This paper describes a general study of the structural characteristics of chromium plate and of the mechanism of chromium plating. New fundamental data are presented on the crystal structure of chromium deposited from chromic acid solutions. In view of deposition conditions producing the various structural modifications, a hypothesis for the plating mechanism is presented.Solution composition and other plating factors can be adjusted so that chromium deposits either as metal in the body-centered cubic (B.C.C.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1

Year Published

1949
1949
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(54 citation statements)
references
References 0 publications
0
53
1
Order By: Relevance
“…1-3).) Both these hydrides were originally formed by cathodic electrodeposition of Cr, 4) but one of them (hcp) was later synthesized by direct reaction with high pressure H 2 gas as well, 5) and the bcc-hcp boundary was determined in the range of H 2 pressure up to p(H 2 ) = 1.6 GPa and temperature up to T 700 K. 6,7) The structure of the hcp hydride was determined by neutron diffraction to be of NiAs type with Cr atoms occupying the As sites, 8) and its composition was close to x = [H]/[Cr] = 1.0. The hydrogen concentration of the fcc hydride appeared to be higher (x ≥ 1.0), and was initially identified with dihydride of CaF 2 type by analogy with other metal-hydrogen systems, 9) but in fact rather variable depending on the condition of sample preparation.…”
Section: Introductionmentioning
confidence: 99%
“…1-3).) Both these hydrides were originally formed by cathodic electrodeposition of Cr, 4) but one of them (hcp) was later synthesized by direct reaction with high pressure H 2 gas as well, 5) and the bcc-hcp boundary was determined in the range of H 2 pressure up to p(H 2 ) = 1.6 GPa and temperature up to T 700 K. 6,7) The structure of the hcp hydride was determined by neutron diffraction to be of NiAs type with Cr atoms occupying the As sites, 8) and its composition was close to x = [H]/[Cr] = 1.0. The hydrogen concentration of the fcc hydride appeared to be higher (x ≥ 1.0), and was initially identified with dihydride of CaF 2 type by analogy with other metal-hydrogen systems, 9) but in fact rather variable depending on the condition of sample preparation.…”
Section: Introductionmentioning
confidence: 99%
“…In the present investigation, the densities of tubes of chromium were determined for each of the following conditions: "as deposited, " after heating at 193 0 0 (in boiling ethylene glycol) and after a second heating in h elium at 440 0 O. The densities wer e 6.95 gjcm 3 as plated, 7.01 gjcm 3 after h eating at 193 0 0 , and 7.09 gjcm 3 after heating at 440 0 O. Brenner [9] indicated that changes in the volume of chromium on heating were isotropic. H ence, heating at 200 0 0 would tend to reduce the volume of the plated chromium.…”
Section: Discussion Of Causes Of Effects Of Chromiummentioning
confidence: 98%
“…Large quantiti es of hydrogen are produced at the cathode, and the chromium plate has b een shown to contain as much as 128 volumes of hydrogen per volume of chromium [5,6]. Theori es explaining the manner in which the cathodic hydrogen is h eld in the chromium [7] have been proposed but are not pertinent to the discussion at this point. Zapffe [8] has explained brittlen ess observed in bend tests on wire plated with chromium as due to hydrogen.…”
Section: Discussion Of Causes Of Effects Of Chromiummentioning
confidence: 99%
“…The nano/micro Cr particles are randomly distributed on the Al substrate with different sizes because the barrier layer is totally dissolved at some positions and partially dissolved at others. Concurrently with Cr deposition, hydrogen bubbles are arising from H + reduction at totally dissolved barrier layer regions of the (PAA/Al) cathode and escape from the surface as H 2 gas [37,38]. At high current density, large number of hydrogen bubbles is created on the PAA/Al substrate during the Cr deposition (Fig.…”
Section: IIImentioning
confidence: 99%